Study of the territorialization of citizen insecurity as a territorial component in Guayaquil, Ecuador. - Ramírez Aguilar, Derly Tamara; Revilla Espinoza, Maytte Ivonne (Artes: Architecture, Technology and Sustainability, 2023)
Insecurity as a structuring component of the territory has developed in Ecuador as deficient management since instruments of public policies and citizen control are not used. In the present research work, the situation of the City of Guayaquil case study is evaluated, and the level of insecurity in the polygon indicated between Av. De las Américas, Av. Kennedy, Av. Delta and Av. José Santiago Castillo. The study analyzed the possible causes of insecurity, among which is the lack of police units in the area. The methodology is oriented towards the qualitative and quantitative analysis of the problem using participant observation. In addition to a comparative study of the level of insecurity depending on the type of crime. Finally, the mapping of urban voids, police points, and public lighting that indicates the areas was developed using the ArcGIS software. It is concluded that insecurity is most
Keywords: Uncertainty; Repression; Perception of insecurity; Social Disorder